A study on the control of melting ratio to increase mechanical properties of laser welded joints between AISI 440C and AISI 430F. (May 2015) - Romoli, L.; Rashed, C.A.A.; Lovicu, G.; Ishak, R.
Abstract: Laser beam welding of dissimilar AISI 440C and AISI 430F stainless steels was investigated in a circular constrained configuration. The beam incidence angle and the offset of the focusing position respect to the contact point between the two materials were used as main control parameters to vary the melting ratio inside the seam. The objective of the study is twofold: to avoid surface microcracks related to the high percentage of carbon of the martensitic steel and to enhance the shear strength of the weld by making it less brittle. To reach this scope the effects of incidence angle and offset on weld bead geometry and melting ratio were studied by means of metallographic analyses, microstructure and microhardness characterization. As last step, the weld mechanical strength was tested by tensile-shear stress test on the whole seam. Experiments demonstrated that varying incidence angle and offsetting the focal position is a reliable method to modify the melting ratio and maintaining the expected resistance length at the material interface, as well. It was found that increasing the percentage of ferritic steel into the joint has beneficial effects on the weld quality and on the shear resistance. The critical carbon content determining the mechanical properties in the fusion zone can be calculated by taking into account the melting ratio. Highlights: AISI 440C and 430F were welded in circular constrained configuration. Melting ratio was controlled by laser incidence angle and focusing position. Increasing ferrite into the joint has beneficial effects on shear resistance. Melting ratio is a good indicator of the carbon content on the fusion zone. Controlling melting ratio enables reduction of solidification defects.